Hyponatraemia in the first week of life in preterm infants. Part II. Sodium and water balance. Issue 5 (May 1984) - Rees, L; Shaw, J C; Brook, C G; Forsling, M L
Abstract : Serial measurements of plasma sodium, sodium balance, water intake, and urine volume were made for a mean period of 5.9 days in 10 preterm infants of mean gestation 30.5 weeks and mean birthweight 1506 g. In five infants weighed regularly, estimates of insensible water loss averaged 2.6 (range 1.4 to 6.2) ml/kg/hour. High insensible water losses were the cause of hypernatraemia that occurred in two of the 10 infants. Net sodium balance was negative during the study and represented contraction of the extracellular fluid volume associated with weight loss. The negative sodium balance did not seem diminished by increasing sodium intake and there was no evidence that sodium intake need exceed 3 to 4 mmol/kg/day. Hyponatraemia was not due to changes in sodium balance but to water retention associated with inappropriate increases in urinary arginine vasopressin excretion and urine osmolality in 8 of 10 infants. Frequent, accurate measurements of body weight and of plasma sodium are the two most reliable indicators of changes in water balance.